Supply Chain Management Strategy to Increase Product Availability - Farida Farida (Jurnal Info Sains : Informatika dan Sains, 2023)
Optimal product availability is the key to success in meeting market demand and maintaining customer satisfaction. This research aims to analyze and develop effective supply chain management strategies to increase product availability in an organization. This research uses a qualitative approach with descriptive methods. The research results show that implementing supply chain management strategies, such as building strong partnerships with suppliers, implementing information technology and automation, and careful risk management, has a positive impact on product availability and on-time delivery. Companies that successfully adopt this combination of strategies are able to increase supply chain operational efficiency, reduce the risk of delays, and respond more adaptively to market changes. By focusing on effective inventory management and data analysis for demand prediction, the company was also able to increase precision in product planning and deployment, providing a strong foundation for increased responsiveness to changing market conditions.